ChemInform Abstract: Synthesis of Bis(oxazoline) Ligands Possessing C‐5 gem‐Disubstitution and Their Application in Asymmetric Friedel—Crafts Alkylations. Issue 9 (February 2016) - O'Reilly, Steven; Aylward, Miriam; Keogh‐Hansen, Caoimhe; Fitzpatrick, Brian; McManus, Helen A.; Mueller‐Bunz, Helge; Guiry, Patrick J.
Abstract: High levels of enantioselectivities are obtained for the conversion of compound (I) with the C5 gem‐disubstituted ligand (BOX), whereas for the conversion of compound (IV) the best enantioselectivity is achieved with ligand (BXB).